Compara????o das demandas metab??licas, cardiorrespirat??rias e de percep????o do esfor??o durante atividades de vida di??ria entre pacientes com bronquiectasia e indiv??duos saud??veis - Nunes, Carina Silveira Mariano (2014)
Introduction: Physiological responses during activities of daily living (ADLs) have never been studied in adult patients with bronchiectasis (BCT). Aim: To compare the metabolic and ventilatory demands, gas exchange and perception of effort during five ADLs between adults with BCT and healthy subjects. Methods: Thirty-nine subjects [27 women; FEV1 61 ?? 26, %pred, MRC 3 (2 ??? 3)] and twenty healthy subjects (14 women) performed the following five ADL: (1) putting on socks, shoes, and vest, (2) putting away different weights on a rack, (3) sweeping a floor, (4) carrying weight while walking (5Kg), and (5) climbing stairs during a minute. Activities 2, 3, and 4 were performed by five minutes. Pulmonary gas exchange was measured during all ADLs. Results: Patients used a higher proportion of metabolic and ventilatory demands, and had a higher perception of effort when compared with healthy subjects. The distance walked in ADL4 was similar between groups; however patients climbed lower number of steps than control group. Conclusions: Patients with BCT have high metabolic and ventilatory demands, with a higher perception of effort to perform simple daily activities when compared to healthy subjects.